IQRA' Buletin Perpustakaan Tun Abdul Razak Bil.6/2022 Jun / Perpustakaan Tun Abdul Razak - UiTM, Perpustakaan Tun Abdul Razak (Perpustakaan Tun Abdul Razak, 2022)
Perpustakaan Tun Abdul Razak menerbitkan eBuletin IQRA bagi keluaran Jun 2022.